Sex and age as biological determinants of autoimmune skin diseases - T. V. Nikolaeva; L. G. Voronina; N. P. Setko (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To study and analyze the relationship of autoimmune diseases of the skin to sex and age. Materials and methods. Study of the relationship of autoimmune of skin diseases to sex and age was performed using contingency table analysis methods, which included the implementation of Pearson x2 to test the hypothesis of independence of the two nominal attributes, calculation of standardized residual values, mapping the relevant category attributes using the method of correspondence analysis, calculation of coefficients of communication Pearson, Chuprova and Kramer. Differences were recognized to be statistically significant at the observed level of significance p < 0,05. In the analysis of standardized residuals were established the following conditions: if the absolute value of the standardized residuals ≥ 2, it was considered that the differences between the observed and expected frequencies are statistically significant at the 0,05 level, if standardized residue ≥ 2,6 the differences are significant at 0,01, if the residue standardized ≥ 3,3 the differences are significant at the 0,001 level. Results. Autoimmune skin diseases linked to sex and age of patients. Vitiligo is associated with male sex, localized scleroderma with women. Sex as a biological factor does not affect the appearance of alopecia areata, lupus erythematosus and bullous dermatosis. Age has in general a greater influence on the formation of autoimmune dermatoses. Alopecia areata is associated in the age period 0-14 and 30-44 years, vitiligo with age period 18-29 years, bullous dermatosis linked to the age group 60 years and older. Conclusion. Sex and age have a differential impact on the formation of autoimmune dermatoses, as biological risk factors of their formation.